Impairment of the phosphotransfer network and performance in broiler chickens experimentally infected by Eimeria spp.: The role of the oxidative stress - Fortuoso B.F.* (2019)
© 2019 Elsevier B.V.The aim of this study was to evaluate whether infection Eimeria spp. in broiler chickens could negatively affect seric enzymes linked to adenosine triphosphate (ATP) metabolism and its relationship to oxidative stress. For this, 30 broiler chickens, 27 days-old, were divided into two groups (n = 15): the control group (C) and the group infected by Eimeria spp. (I). On days 1, 7 and 15 of the experiment, the animals were weighed, and fecal and blood samples were collected to evaluate the presence of oocysts and for serum biochemistry and enzymatic parameters, respectively. On day 15, one animal per repetition was submitted to euthanasia and intestinal fragments were collected for histopathological analyses. The body weight was lower in infected animals on day 15 of experiment, while oocyst counts were higher in infected animals on days 7 and 15 of the experiment. Serum levels of globulins were lower in infected animals on days 7 and 15 of experiment, while uric acid levels were higher in the same days, which represent changes on the immune system. Compared to the uninfected animals, on days 7 and 15, levels of serum globulins, triglycerides, creatine kinase and cholesterol were lower. Levels of adenylate kinase and reactive oxygen species (ROS) were higher on both days in infected animals, while levels of thiobarbituric acid-reactive substances (TBARS) were elevated on day 15. Lesions and immature forms of the parasite were observed in the intestines of infected birds. The phosphotransfer network elicited by an oxidative stress negatively affected the performance of broiler chickens with coccidiosis.